Effects of lava heating on volatile‐rich slopes on Io. Issue 3 (20th March 2017) - Dundas, Colin M.
Abstract: The upper crust of Io may be very rich in volatile sulfur and SO2 . The surface is also highly volcanically active, and slopes may be warmed by radiant heat from the lava. This is particularly the case in paterae, which commonly host volcanic eruptions and long‐lived lava lakes. Patera slopes are highly variable, but some are greater than 70°. I model the heating of a volatile slope for two end‐member cases: instantaneous emplacement of a large sheet flow and persistent heating by a long‐lived lava lake. In general, single flows can briefly raise sulfur to the melting temperature or drive a modest amount of sublimation of SO2 . Persistently, lava‐covered surfaces will drive much more significant geomorphic effects, with potentially significant sublimation and slope retreat. In addition to the direct effects, heating is likely to weaken slope materials and may trigger mass wasting. Thus, if the upper crust of Io is rich in these volatile species, future missions with high‐resolution imaging are likely to observe actively retreating slopes around lava lakes and other locations of frequent eruptions. Key Points: Sustained lava heating can modify volatile slopes on Io Single lava flows drive little melting If Io's upper crust is volatile‐rich, paterae may be actively modified